Peran Kegiatan Ekstrakurikuler dalam Pengembangan Keterampilan Sosial Siswa - Marpaung, Dian Pratiwi Br.; Nurroyian; Hasbih Sholeh Suryadi; Lucky Tirta Ardiansyah; Muhammad Iqbal (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Extracurricular activities have a strategic role in developing students' social skills. Social skills are valuable provisions for students to interact effectively, build positive relationships, and contribute optimally in society. This research aims to examine the role of extracurricular activities in developing students' social skills. This research uses a type of research approach in the form of a literature study (library research) where heritage studies are a study used to collect information and data with the help of various kinds of materials in libraries such as documents, books, magazines, historical stories and others.. The results showed that social skills are the ability to interact with others in a social context in a way that is socially acceptable and valuable. These skills include the ability to communicate orally and in writing, solve everyday problems, understand, evaluate and work with others. And extracurricular activities are activity programs that take place outside of programmed school hours. Researchers realize that there are many shortcomings in the articles that have been compiled, so researchers expect suggestions from readers to improve this article. And the researcher hopes that this article is useful for all readers